2010
DOI: 10.1080/09602010903529610
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Interviewing to promote self-awareness and engagement in rehabilitation following acquired brain injury: A conceptual review

Abstract: The benefits of rehabilitation following acquired brain injury (ABI) are all too often disrupted by a lack of engagement in the process, variously attributed to cognitive, emotional and neurobehavioural sequelae, and prominently to impaired self-awareness of deficits. Motivational Interviewing (MI) has been widely applied to address treatment adherence in health settings, including a small but emerging evidence base in brain injury contexts. A conceptual review of the literature is offered, examining the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
87
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(91 citation statements)
references
References 108 publications
3
87
1
Order By: Relevance
“…Of those studies utilising this technique, MI was either found not to be more effective than goal setting alone (Corrigan et al, 2005) or its effects were not sufficiently measured (Hsieh, Ponsford, Wong, Schönberger, Taffe & Mckay, 2012;Hsieh, Ponsford, Wong, Schönberger, Mckay & Haines, 2012). This appears to contradict the suggestion of others (Medley & Powell, 2010;Holloway, 2012). It is possible that MI is effective in increasing motivation for rehabilitation in this group, but that the design of the studies reviewed here was insufficient for evaluation.…”
Section: Discussioncontrasting
confidence: 53%
“…Of those studies utilising this technique, MI was either found not to be more effective than goal setting alone (Corrigan et al, 2005) or its effects were not sufficiently measured (Hsieh, Ponsford, Wong, Schönberger, Taffe & Mckay, 2012;Hsieh, Ponsford, Wong, Schönberger, Mckay & Haines, 2012). This appears to contradict the suggestion of others (Medley & Powell, 2010;Holloway, 2012). It is possible that MI is effective in increasing motivation for rehabilitation in this group, but that the design of the studies reviewed here was insufficient for evaluation.…”
Section: Discussioncontrasting
confidence: 53%
“…More research is needed in order to identify reasons why MS patients either do or do not adhere to cognitive training interventions. Future studies should consider utilizing regular phone check-ins that involve motivational interviewing counseling techniques to improve adherence rates (Medley & Powell, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…Several authors have argued the benefits of rehabilitation are limited if the patient is not fully engaged in the process [2,3]. For example, levels of engagement have been associated with improved functional improvement during inpatient rehabilitation and levels of functioning after discharge.…”
Section: Introductionmentioning
confidence: 99%